IMPROVING STUDENTS MASTERY OF SIMPLE PRESENT TENSE IN DESCRIPTIVE TEXT BY USING KAHOOT! GAME - Pratiwi, Rika; Susilawati, Endang; Wardah, Wardah (Journal of English Education Program, 2020)
The aim of this research was to improve students mastery of simple present tense in descriptive text by using Kahoot! game. This research was a classroom action research that was done in three cycles. The subject for this research was the tenth-grade students in class X IIS 2. The writer observed students improvement in mastering the simple present tense by collecting data through observation checklist, field notes and multiple choices test. The students attitude towards the learning process was gathered by observation checklist and field notes. The data of students mastery in simple present tense was obtained by the students test which was assessed through scoring rubric. The result showed that students problems in simple present tense in the form of verb (to be) and verb (-s,-es) of the third person singular had been solved by using Kahoot! game as media for teaching, by providing picture in each question of Kahoot! game, by setting time limit in the game to encourage students participation, a music in the Kahoot! game created positive attitude in the classroom and the questioning improved the students attention and motivation in remembering the rules of simple present tense. Furthermore, the students interest in learning the simple present tense also improved. In conclusion, the media was able to improve the students mastery of simple present tense in descriptive text. The writer recommends the teacher to use Kahoot! game as media in teaching and learning process, especially in teaching simple present tense with the similar problems.